2023
DOI: 10.1021/acs.chemrev.3c00168
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Blue Energy Based on Salinity and Temperature Gradient: Challenges, Solutions, and Opportunities

Masoud Rastgar,
Kazem Moradi,
Cassie Burroughs
et al.

Abstract: Greenhouse gas emissions associated with power generation from fossil fuel combustion account for 25% of global emissions and, thus, contribute greatly to climate change. Renewable energy sources, like wind and solar, have reached a mature stage, with costs aligning with those of fossil fuel-derived power but suffer from the challenge of intermittency due to the variability of wind and sunlight. This study aims to explore the viability of salinity gradient power, or “blue energy”, as a clean, renewable source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 357 publications
0
10
0
Order By: Relevance
“…In addition to proton gradient energy, industrial waste heat, known as low-grade heat, shows great potential when coupled with osmotic energy. 24 We found that as the temperature of the electrolyte solution increases, the conversion efficiency of proton gradient energy is enhanced, with a power density of 8.1 W/m 2 at 333 K (5.1 W/m 2 at 293 K) under a test area of 0.2 mm 2 . This work demonstrates the potential application of a low-cost commercial Nafion membrane in proton gradient energy harvesting and provides ideas for large-scale conversion of osmotic energy.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition to proton gradient energy, industrial waste heat, known as low-grade heat, shows great potential when coupled with osmotic energy. 24 We found that as the temperature of the electrolyte solution increases, the conversion efficiency of proton gradient energy is enhanced, with a power density of 8.1 W/m 2 at 333 K (5.1 W/m 2 at 293 K) under a test area of 0.2 mm 2 . This work demonstrates the potential application of a low-cost commercial Nafion membrane in proton gradient energy harvesting and provides ideas for large-scale conversion of osmotic energy.…”
Section: Introductionmentioning
confidence: 82%
“…Even under a large area of 12.5 mm 2 in a strong acidic environment, a power density of 2.1 W/m 2 can be achieved. In addition to proton gradient energy, industrial waste heat, known as low-grade heat, shows great potential when coupled with osmotic energy . We found that as the temperature of the electrolyte solution increases, the conversion efficiency of proton gradient energy is enhanced, with a power density of 8.1 W/m 2 at 333 K (5.1 W/m 2 at 293 K) under a test area of 0.2 mm 2 .…”
Section: Introductionmentioning
confidence: 93%
“…We should note that without solar light osmotic power can still be generated, albeit with lower power density. Moreover, industrial wastewater often has relatively high temperature, which should also promote the Na + selectivity and the osmotic power density. ,,, Such power harvesting is environmentally safe and may offer the possibility of generating net energy and economic profit from the simultaneous treatment of wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the scarcity of fossil fuels, renewable energy sources and energy storage devices have attracted considerable attention. Particularly, supercapacitors have received increasing attention because of their high capacitance, good stability, and fast charging and discharging processes. Pseudocapacitor is a type of supercapacitor, whose mechanism was originally demonstrated by the redox reactions of RuO 2 in aqueous electrolytes. , Notably, the electrode materials play a key role in the performance of supercapacitors; however, their high cost makes them not suitable for mass production.…”
mentioning
confidence: 99%